Effects of strain rate due to SMAW welding on mechanical properties of AISI 1005 low alloy steel. Issue 1 (May 2020) - Husaini; Akbary, K; Hasanuddin, I; Putra, T E; Husin, H
Abstract: The welding process can affect the mechanical properties of the metal. This study was aimed at examining the effects of welding on the strain rate of AISI 1005 carbon steel. Shield metal arc welding, utilizing an E6013 electrode with a diameter of 2.5 mm, a double V-notch with an angle of 120°, and a welding position of 1G, was used to weld low carbon steel. A tensile test was performed to determine the mechanical properties of the steel at various strain rates to represent the loads that it would be subjected to. The test was performed at strain rates of 3 mm/min, 9 mm/min, 15 mm/min and 20 mm/min. The results showed that as the strain rate of steel increased to 20 mm/min, the maximum tensile strength of 447.67 MPa and highest yield strength of 362.94 MPa were obtained, while the lowest values were obtained at a strain rate of 3 mm/min. An examination of the fractured surfaces using SEM showed that at the strain rates of 3 mm/min, 15 mm/min and 20 mm/min smaller voids were formed.